Integration of whole‐genome sequencing and functional screening identifies a prognostic signature for lung metastasis in triple‐negative breast cancer. Issue 10 (29th April 2019) - Xie, Guangdong; Yang, Haiyuan; Ma, Ding; Sun, Yihua; Chen, Haiquan; Hu, Xin; Jiang, Yi‐Zhou; Shao, Zhi‐Ming
Abstract : Lung metastasis is one of the leading causes of death for triple‐negative breast cancer (TNBC). We sought to characterize the genetic alterations underlying TNBC lung metastases by integrating whole‐genome sequencing and functional screening. Furthermore, we aimed to develop a metastasis‐related gene signature for TNBC patients to improve risk stratification. In this prospective observational study, we first conducted whole‐genome sequencing of paired primary tumor and lung metastasis from one TNBC patient to identify potential genetic driver alterations. An in vivo gain‐of‐function screening using an amplified open reading frame library was then employed to screen candidate genes promoting lung metastasis. Finally, we applied Cox proportional hazard regression modeling to develop a prognostic gene signature from 14 candidate genes in TNBC. Compared to the primary tumor, copy number amplifications of chromosomes 3q and 8q were identified in the lung metastasis. We discovered an enrichment of 14 genes from chromosomes 3q and 8q in mouse lung metastases model. We further developed and validated a four‐gene signature ( ENY2, KCNK9, TNFRSF11B and KCNMB2 ) that predicts recurrence‐free survival and lung metastasis in TNBC. Our data also demonstrated that upregulated expression of ENY2 could promote invasion and lung metastasis of TNBC cells both in vitro and in vivo . In conclusion, our study reveals functional genes with copy number amplifications among chromosome 3q and 8q in lung metastasis of TNBC. And we develop a functional gene signature that can effectively stratify patients into low‐ and high‐risk subgroups of recurrence, helping frame personalized treatments for TNBC. Abstract : What's new? Next‐generation whole‐genome sequencing has allowed the comprehensive characterization of genomic changes in the process of metastasis, but often the biological function or clinical relevance of these variants remains unclear. By using an approach combining whole‐genome sequencing and functional screening to seek genetic alterations underlying lung metastasis in triple‐negative breast cancer (TNBC), here the authors reveal several functional genes with copy number amplifications among chromosome 3q and 8q. Moreover, they present a functional four‐gene signature that can effectively stratify patients into low‐ and high‐risk subgroups of recurrence and could help frame personalized treatments for TNBC.